1999
DOI: 10.1159/000045363
|View full text |Cite
|
Sign up to set email alerts
|

The Role of α-Glutathione S-Transferase in the Monitoring of Hemodialysis Patients with Hepatitis C Virus Infection Undergoing High-Dose Interferon-α-2b Therapy

Abstract: The study aimed to evaluate the behavior of α-glutathione S-transferase (α-GST) in the serum of hemodialysis patients with hepatitis C virus (HCV) infection following treatment with high-dose IFN-α-2b. Ten patients with detected anti-HCV antibodies and HCV RNA by RT-PCR were selected and treated with high-dose interferon (IFN)-α-2b, 10 million units s.c. daily for 2 weeks followed by 3 times per week for 6 additional weeks. Blood samples were obtained from these patients at baseline for plasma α-GST and hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…We analysed the subgroup of controlled trials in order to compare drop-outs in study (patients who received conventional IFN monotherapy) vs control groups (patients who did not receive antiviral agents), but only Fernandez et al [24] gave information on this point (21.4% vs 22.2%, NS). The profile [26] 27.3% (3 ⁄ 11) 100% (11 ⁄ 11) 0% (0 ⁄ 6) 100% (6 ⁄ 6) Uchihara et al [27] 33.3% (3 ⁄ 9) NA 100% (1 ⁄ 1) NA Benci et al [28] 20% (2 ⁄ 10) NA 20% (2 ⁄ 10) 60% (6 ⁄ 10) Huraib et al [32] 70.6% (12 ⁄ 17) 88% (15 ⁄ 17) 67% (4 ⁄ 6) 83% (5 ⁄ 6) Campistol et al [30] 42.1% (8 ⁄ 19) 74% (14 ⁄ 19) 100% (10 ⁄ 10) 100% (10 ⁄ 10) Boran et al [29] 30% (3 ⁄ 10) NA 30% (3 ⁄ 10) NA Espinosa et al [35] 46.1% (6 ⁄ 13) 61% (8 ⁄ 13) 61% (6 ⁄ 13) 69% (9 ⁄ 13) Casanovas-Taltavull et al [33] 62.1% (18 ⁄ 29) 83% (24 ⁄ 29) NA 79% (23 ⁄ 29) Hanrotel et al [31] 33.3% (4 ⁄ 12) 75% (9 ⁄ 12) NA NA Sporea et al [36] 38.5% ( Koenig et al [22] 35% (13 ⁄ 37) Septicaemia (n = 3), fever (n = 1), diarrhoea (n = 9) Pol et al [23] 5% (1 ⁄ 19) Anaemia Raptopoulou-Gigi et al [24] 31% (6 ⁄ 19) Fever (n = 1), leucopenia (n = 1), pericarditis (n = 1), myalgias (n = 2), thromboembolism (n = 1) Fernandez et al [25] 21% (3 ⁄ 14) Leucopenia (n = 2), depression (n = 2) Uchihara et al [27] 33% (3 ⁄ 9) Fever (n = 2), depression (n = 1) Benci et al [28] 10% (1 ⁄ 10) Fever Huraib et al [32] 6% (1 ⁄ 17) Lethargy Campistol et al [30] 53% (10 ⁄ 19) Flu-like symptoms (n = 4), leucopenia (n = 3), anaemia (n = 1), depression (n = 1), diarrhoea (n = 1) Espinosa et al [35] 23% (3 ⁄ 13) Seizures (n = 1), flu-like symptoms (n = 1), leucopenia (n = 1) Casanovas-Taltavull et al [33] 24% (7 ⁄ 29) Depression (n = 1), fever (n = 2), cholecystitis (n = 1), heart failure (n = 1), hepatoxicity (n = 1), pericarditis (n = 1) Hanrotel et al [31] 8% (1 ⁄ 12) Rejection non-functioning kidney graft (n = 1) Sporea et al [36] 27.7% (5 ⁄ 18) Thrombocytopenia (n = 3) Degos et al [34] 51% (19 ⁄ 37) Seizures (n = 1), depression (n = 1), cardiovascular disorders (n = 4), pancreatitis (n = 1), diarrhoea (n = 1), astenia (n = 9), anorexia (n = 1), rejection nonfunctioning graft (n = 1) Ozdemir et al [38]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We analysed the subgroup of controlled trials in order to compare drop-outs in study (patients who received conventional IFN monotherapy) vs control groups (patients who did not receive antiviral agents), but only Fernandez et al [24] gave information on this point (21.4% vs 22.2%, NS). The profile [26] 27.3% (3 ⁄ 11) 100% (11 ⁄ 11) 0% (0 ⁄ 6) 100% (6 ⁄ 6) Uchihara et al [27] 33.3% (3 ⁄ 9) NA 100% (1 ⁄ 1) NA Benci et al [28] 20% (2 ⁄ 10) NA 20% (2 ⁄ 10) 60% (6 ⁄ 10) Huraib et al [32] 70.6% (12 ⁄ 17) 88% (15 ⁄ 17) 67% (4 ⁄ 6) 83% (5 ⁄ 6) Campistol et al [30] 42.1% (8 ⁄ 19) 74% (14 ⁄ 19) 100% (10 ⁄ 10) 100% (10 ⁄ 10) Boran et al [29] 30% (3 ⁄ 10) NA 30% (3 ⁄ 10) NA Espinosa et al [35] 46.1% (6 ⁄ 13) 61% (8 ⁄ 13) 61% (6 ⁄ 13) 69% (9 ⁄ 13) Casanovas-Taltavull et al [33] 62.1% (18 ⁄ 29) 83% (24 ⁄ 29) NA 79% (23 ⁄ 29) Hanrotel et al [31] 33.3% (4 ⁄ 12) 75% (9 ⁄ 12) NA NA Sporea et al [36] 38.5% ( Koenig et al [22] 35% (13 ⁄ 37) Septicaemia (n = 3), fever (n = 1), diarrhoea (n = 9) Pol et al [23] 5% (1 ⁄ 19) Anaemia Raptopoulou-Gigi et al [24] 31% (6 ⁄ 19) Fever (n = 1), leucopenia (n = 1), pericarditis (n = 1), myalgias (n = 2), thromboembolism (n = 1) Fernandez et al [25] 21% (3 ⁄ 14) Leucopenia (n = 2), depression (n = 2) Uchihara et al [27] 33% (3 ⁄ 9) Fever (n = 2), depression (n = 1) Benci et al [28] 10% (1 ⁄ 10) Fever Huraib et al [32] 6% (1 ⁄ 17) Lethargy Campistol et al [30] 53% (10 ⁄ 19) Flu-like symptoms (n = 4), leucopenia (n = 3), anaemia (n = 1), depression (n = 1), diarrhoea (n = 1) Espinosa et al [35] 23% (3 ⁄ 13) Seizures (n = 1), flu-like symptoms (n = 1), leucopenia (n = 1) Casanovas-Taltavull et al [33] 24% (7 ⁄ 29) Depression (n = 1), fever (n = 2), cholecystitis (n = 1), heart failure (n = 1), hepatoxicity (n = 1), pericarditis (n = 1) Hanrotel et al [31] 8% (1 ⁄ 12) Rejection non-functioning kidney graft (n = 1) Sporea et al [36] 27.7% (5 ⁄ 18) Thrombocytopenia (n = 3) Degos et al [34] 51% (19 ⁄ 37) Seizures (n = 1), depression (n = 1), cardiovascular disorders (n = 4), pancreatitis (n = 1), diarrhoea (n = 1), astenia (n = 9), anorexia (n = 1), rejection nonfunctioning graft (n = 1) Ozdemir et al [38]…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study does not support the use of pegylated IFN in dialysis patients with chronic hepatitis C, as no benefit on virological response was seen (the summary estimate for SVR being 31%) and a high drop-out rate occurred (overall estimate for drop-out rate was 27%). IFNa-2b 24 3 · 10 6 UI · 3 Raptopoulou-Gigi et al [24] IFNa-2b 24 1-3 · 10 6 UI · 3 Fernandez et al [25] Recombinant-IFNa-2b 24 1.5-3 · 10 6 UI · 3 Chan et al [26] IFNa-2b 24 3 · 10 6 UI · 3 Uchihara et al [27] Recombinant ⁄ natural IFNa 24 3 · 10 6 UI · 7 (2 weeks) + 3 · 10 6 · 3 (22 weeks) 3 · 10 6 UI · 3 (n = 3) Benci et al [28] Leucocyte-IFNa 48 1 · 10 3 UI · 3 Huraib et al [32] IFNa 48 3 · 10 6 UI · 3 Campistol et al [30] IFNa-2b 24 3 · 10 6 UI · 3 Boran et al [29] IFNa-2b 8 10 · 10 6 UI · 7 (2 weeks) 3 · 10 6 UI · 3 (6 weeks) Espinosa et al [35] IFNa 48 3 · 10 6 UI · 3 Casanovas-Taltavull et al [33] Lymphoblastoid-IFNa 48 3-1.5 · 10 6 UI · 3 Hanrotel et al [31] IFNa-2a 48 3 · 10 6 UI · 3 Sporea et al [36] IFNa-2b 24-48 3 · 10 6 UI · 7 (2 weeks) 3 · 10 6 UI · 3 Degos et al [34] IFNa-2b 48 3 · 10 6 UI · 3 Kamar et al [37] IFNa 24-48 3 · 10 6 UI · 3 Ozdemir et al [38] IFNa-2b 24-48 3-6 · 10 6 UI · 3 Grgurevic et al [45] IFNa 24 3 · 10 6 UI · 3 (n = 8) 5 · 10 6 UI · 3 + 5 · 10 6 UI · 1 (n = 7) Rivera et al [40] IFNa-2b 24-48 3 · 10 6 UI · 3 Mahmoud et al [39] IFNa-2b 24 3 · 10 6 UI · 3 Rocha et al [41] IFNa 48 3 · 10 6 UI · 3 Yildirim et al [44] IFNa-2a 24-48 3 · 10 6 UI · 3 Chow et al [43] IFNa-2a 48 3 · 10 6 UI · 3 Buargub et al [42] IFNa 48 3 · 10 6 UI · 3 Sporea et al [46] PegIFN-alpha2a 48 180 lg ⁄ week Russo et al [47] PegIFN-alpha2b 48 1.0-0.5 lg ⁄ kg ⁄ week Covic et al [48] PegIFN-alpha2a 48 135 lg ⁄ week Kokoglu et al [49] PegIFN-alpha2a 48 135 lg ⁄ week However, the limited number of patients receiving initial monotherapy by pegylated IFN precluded more definitive conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Benci et al 112 10 Leukocyte IFN-a 1.0 MU 3 times per week for 48 weeks 20 10 Djordjević et al 113 6 IFN-a-2b 3.0 MU 3 times/week for 12 weeks 33 0 Boran et al 114 10 IFN-a-2b 10.0 MU/day for 2 weeks, and 3.0 MU 3 times/week for 6 weeks…”
Section: C-h Liu and J-h Kaomentioning
confidence: 99%
“…The treatment‐related withdrawal rates were 0–53% (Table 4). 105–128 Four meta‐analysis studies showed that approximately one‐third of ESRD patients with chronic hepatitis C who received conventional IFN monotherapy can achieve an SVR 129–133 . However, the corresponding treatment‐related withdrawal rates ranged from 20% to 30%.…”
Section: Treatment Of Esrd Patients With Chronic Hcv Infectionmentioning
confidence: 99%
“…α -GSTs can be used as a more sensitive biomarker of liver function than the conventionally analysed aspartate aminotransferase (AST) and alanine aminotransferase (ALT) because of its lower molecular weight and shorter half-life (3). Multiple studies have pointed to α -GST as an earlier and better marker of liver injury in acetaminophen and alcohol poisoning, HBV (hepatitis B virus) and HCV (hepatitis C virus) infection, allograft rejection, and liver ischemic-reperfusion injury [2, 3, 5, 811]. The main disadvantage of aminotransferases is their uneven distribution in the liver [10, 12].…”
Section: Introductionmentioning
confidence: 99%